2018
DOI: 10.1080/10810730.2018.1448488
|View full text |Cite
|
Sign up to set email alerts
|

How Is Marijuana Vaping Portrayed on YouTube? Content, Features, Popularity and Retransmission of Vaping Marijuana YouTube Videos

Abstract: The purpose of the study is to investigate how vaping marijuana, a novel but emerging risky health behavior, is portrayed on YouTube, and how the content and features of these YouTube videos influence their popularity and retransmission. A content analysis of vaping marijuana YouTube videos published between July 2014 to June 2015 (n = 214) was conducted. Video genre, valence, promotional and warning arguments, emotional appeals, message sensation value, presence of misinformation and misleading information, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…The operationlization of theme was adapted by a previous content analysis conducted by Sinnenberg and colleagues (2016), who categorized the semantic content of tweets into risk factor , awareness , treatment and management , mechanism , outcomes , symptoms , prevention , and support (see Table 2). The source was coded as individuals (e.g., John Moss; Michael), health-related organizations (e.g., U-M Health System), and non-health-related organizations (e.g., WiFi in Japan), which was adapted from previous content analytic health communication studies on social media (e.g., Stellefson et al, 2014; Yang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The operationlization of theme was adapted by a previous content analysis conducted by Sinnenberg and colleagues (2016), who categorized the semantic content of tweets into risk factor , awareness , treatment and management , mechanism , outcomes , symptoms , prevention , and support (see Table 2). The source was coded as individuals (e.g., John Moss; Michael), health-related organizations (e.g., U-M Health System), and non-health-related organizations (e.g., WiFi in Japan), which was adapted from previous content analytic health communication studies on social media (e.g., Stellefson et al, 2014; Yang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…For studies on noncommunicable diseases (9/69) or treatments (5/69), YouTube was the most used social media platform. Overall, health misinformation was most prevalent in studies related to smoking products, such as hookah and water pipes [33,59,71], e-cigarettes, and drugs, such as opioids and marijuana [45,70,97]. Health misinformation about vaccines was also very common.…”
Section: Prevalence Of Health Misinformationmentioning
confidence: 99%
“…According to topic, regarding drug and opioid use, studies investigated the dissemination of misinformation through social media platforms [32,45,46,70,97], the consumption of misinformation related to these products, drug abuse, and the sale of online medical products [61,66]. These studies highlighted the risk, especially for young people, caused by the high rate of misinformation related to the dissemination of drug practice and misuse (predominantly marijuana and opioids) [45].…”
Section: Drugs and Smokingmentioning
confidence: 99%
“…Only two studies have examined how cannabis vaping is portrayed on YouTube and were based on videos searched up to 2015. One study by, Krauss and colleagues, examined dabbing [22] and another by Yang et al reviewed video content for cannabis vaping based on videos published between July 2014 and June 2015 [23]. A more recent study identified a number of videos that portrayed modifications to electronic nicotine delivery systems that can be used to deliver substances other than nicotine.…”
Section: Introductionmentioning
confidence: 99%